Eksplorasi Pendekatan Culturally Responsive Teaching dalam Pembelajaran Bahasa Indonesia Kelas 2 di Sekolah Dasar - Arizkylia Yoka Putri; Dini Ludfira Aisyah (PT. PENERBIT TIGA MUTIARA, 2025)
A culturally responsive approach to teaching has become an essential element in building an inclusive, relevant, and transformative educational ecosystem, particularly in the context of Indonesian language instruction at the primary school level. This study aims to analyze the implementation of the Culturally Responsive Teaching (CRT) approach in Indonesian language learning among second-grade students at SDN Sumobito 1 Jombang. Employing a descriptive qualitative method, data were collected through participatory observation, semi-structured interviews, and documentation. The data were thematically analyzed to identify patterns of CRT application in daily teaching practices. The findings indicate that student engagement in the learning process is relatively active; however, the integration of CRT principles remains suboptimal. This is evidenced by the limited use of teaching materials that reflect students' cultural backgrounds and the low level of teachers’ conceptual understanding of the CRT approach. The study underscores the importance of enhancing educators’ professional capacity through continuous training focused on pedagogies that are sensitive to local cultural contexts. In addition, the development of culturally responsive teaching materials needs to be accommodated within the curriculum to make learning more contextual and meaningful. The implications of these findings suggest that a systematic implementation of CRT has the potential to improve the quality of Indonesian language education by positioning cultural diversity as a pedagogical asset rather than a barrier. Consequently, the results of this study are expected to serve as a reference for the formulation of more inclusive, adaptive, and culturally equitable basic education policies in multicultural societies.